Maternal eating behavior associated with body composition of the adolescent son in the population of Allende-Mexico: Conducta alimentaria materna asociada a la composición corporal del hijo adolescente en la población de Allende-México - Cavazos-Flores, Vanessa (2023)
Introduction: Appetite traits (RA) are part of the eating behavior of the person, with a series of continuous responses that are related to the choice and consumption of food, but also to aspects at the moment in which the feeding is carried out, the frequency of meals, the place, the company with which they are shared, among others. These factors can have a significant impact on the way a person eats and on their long-term health. Objective: To analyze the possible connection between maternal eating behavior and the body composition of the adolescent, from a high school in the city of Allende, Nuevo León, in Mexico. Method: A quantitative, cross-sectional and correlational study was carried out. The period of the present study was February-August 2022, the population was 41 couples (mother and adolescent son between 15 and 17 years old), from a high school in the municipality of Allende, Nuevo León, Mexico. To test the hypothesis, Spearman's correlation coefficient was obtained. Results: When running the statistical test, it was found that there is no significant correlation between the level of eating behavior of the mother and the body composition of the adolescent (rs = -0.174, p = 0.277), therefore, the hypothesis of investigation. Conclusions: It was found that the eating behavior of the mother is not significantly related to the body composition of the adolescents with the sample considered in the present study.